Da’wah Education Based on Religious Moderation Training Using Digital Technology at Islamic Boarding Schools in East Bandung - Asep Shodiqin; Nanih Machendrawaty; Dudy Imanuddin Effendi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
Indonesia as one of the great houses of Muslims must be a prototype in the world in developing religious moderation education based on the teachings of Islam rahmatan lil 'alamin. In the context of da’wah education, the issue of religious moderation in Islamic educational institutions, especially Islamic boarding schools, is an effort to prepare the best cadres of teachers who are not only able to read classical books, but also have comprehensive Islamic insight. With the development and progress of the times, the provision of the best teacher cadres in Islamic boarding schools is not only done traditionally but also must be followed by a training model using today's digital technology media. Based on arguments about the importance of preaching education based on religious moderation training using digital technology, this research has focused on Islamic boarding schools in the East Bandung area. This training using digital technology is an effort to increase the literacy of Islamic boarding school teachers and students about religious moderation education. This study uses a participatory observation method, meaning that researchers who involve themselves in the object of research are carried out. The conclusion of this study shows the importance of da’wah education based on religious moderation training by using digital technology in Islamic boarding schools to keep up with the times in the 4.0 revolution era, especially in strengthening religious moderation literacy. Strengthening literacy which has a positive impact to encourage the practice of religious moderation behavior among Islamic boarding schools and the surrounding community, in East Bandung.